Alexithymia and addiction: the mediating role of stress - Salnikova, Alina (Psychosomatic Medicine and General Practice, 2021)
Background. Gambling encourages people to want more money than they did at the beginning of the game. The growing availability and variety of games has made gambling a critical issue. Statistics show that out of 48.5 million Ukrainians, more than four million are players. Objective. The purpose of this study was to determine the extent to which levels of alexithymia and stress may predict pathological gambling. The study also examines the role of stress mediators in the relationship between alexithymia and addiction. Methods. The group of 123 male patients aged 18 to 64 years with a mean of 33 (SD = 11.5) participated in the study. Participants were selected from various rehabilitation centers in Kyiv. The study was conducted only with volunteers over 18 years of age who declared gambling and signed an informed consent. Measuring instruments: 1) Form of demographic information 2) South Oaks Gambling Screen (SOGS) 3) Toronto Alexithymic Scale (TAS-20) 4) Psychological stress measure (PSM-25) 5) Lemyr-Tessier-Fillion PSM-25 scale Data were collected from individuals through online surveys as well as in person. Data were analyzed using the t-test to determine the significance of differences between groups. However, no significant difference was found. Before the participants completed the survey, it was ensured that they all signed the consent form. The data was cleaned after all the data had been entered into the computer. A total of six participants who either did not answer more than half of the questions or had deviations (-3.29> z <3.29) were excluded from the study. Results. Regression analysis showed that the amount of money betting on gambling, the total score of TAS-20 and PSM-25 significantly predicted pathological gambling. In addition, stress has a partial mediating role in the relationship between alexithymia and addiction. Conclusion. It is claimed that people with a high level of alexithymia become prone to gambling addiction due to stress. In addition to alexithymia, stress also plays an important role in the formation of addiction. In this context, this study contributes to the relevant literature by combining alexithymia, stress, and pathological gambling in conjunction with each other.